Current Diagnosis of Infant Tuberculosis Infection. - Antas, Paulo Renato Zuquim (Bentham Science Publishers, 2012)
One of the most extraordinary characteristics of Mycobacterium tuberculosis infection is its capacity to remain within the host's tissues for a long period of time. There is an enormous reservoir of persons latently infected with tuberculosis (LTBI) estimated at about a third of the world's population. From this reservoir arise about 10 million new cases of active TB and more than two million deaths occur annually. Current Diagnosis of Infant Tuberculosis Infection covers problems concerning the diagnosis of LTBI, giving an overview of commercially available options and, unlike most reviews on.